PENGARUH PEMBENTUK FILM PVA PADA SEDIAAN MASKER GEL PEEL-OFF EKSTRAK ETANOL BAWANG DAYAK (Eleutherina palmifolia (L.) Merr) TERHADAP AKTIVITAS ANTIBAKTERI Staphylococcus aureus PENYEBAB JERAWAT - Husnani Husnani; Fitri Sri Rizki (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTDayak Onion (Eleutherine palmifolia) is one of the plants that can inhibit Staphylococcus aureus bacteria that causes acne. This study aims to determine the effect of polyvinyl alcohol on peel-off gel mask preparations from onion dayak ethanol extract on the antibacterial activity of Staphylococcus aureus that causes acne. Extraction using maceration method with 96% ethanol. The concentration of dayak onion extract was made at 5%, 7.5%, and 10% and the peel-off gel mask formula from dayak onion extract with variations in extract concentration were 5%, 7.5%, and 10% based on Polyvinyl Alcohol (PVA). Antibacterial activity is carried out using the disk disc method. In testing the inhibition of dayak onion extract at a concentration of 5% resulted in a clear zone of 15.5 mm, a concentration of 7.5% and 10% producing the same clear zone diameter of 17.1 mm. The peel-off gel mask in formulation I obtained a clear zone diameter of 8.7 mm, formulation II the diameter of the clear zone was 12.2 mm, and formula III the diameter of the clear zone was 15.3 mm. The results of this study indicate that on dayak onion extract has a greater inhibitory power compared to the dayak onion extract peel-off gel mask preparation. It can be concluded that the PVA in the preparation affects the amount of inhibitory power on the bacteria forming acne, namely Staphylococcus aureus.Keywords: Dayak onion extract, Staphylococcus aureus, disk discs, antibacterial inhibitory test, acne-causing bacteria, peel-off gel mask.